Please like me : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Design (Fashion Design) at Massey University, Wellington, New Zealand - Norquay, Tess (Massey University, 2018)
𝘗𝘭𝘦𝘢𝘴𝘦 𝘓𝘪𝘬𝘦 𝘔𝘦 is a fashion collection which aims to critique women’s objectification in its many forms. The objectification of women has long been seen as a concept which exists only within visual media, such as film, television, and advertising. In actuality, it has crept into the ways we see and talk about women. It is now seen as appropriate to apply terms to women which were previously and traditionally only connected to the discussion of product, and product exchange. Women’s objectification was also previously seen as only occurring within the framework of large corporations, a tool and crutch of our capitalist system. One needs only to glance through any social media outlet to disprove this theory. Social media has allowed the memetic spread of misogynist ideas at an unprecedented pace and scope. People from all walks of life, not merely those who stand to gain financially from the insecurities of women, participate in this new application of language. A notable example of this is the internet meme urging men to “take their girl swimming on the first date”, to unveil whether they are “false advertising” through use of cosmetics. While I deny that commodifying language use is limited to the discussion of capitalist practice, I will argue that the prevalence of capitalism has led to this outcome. I have used fashion as my medium for the discussion of this topic because I see correlations in how both fashion and women are perceived academically, culturally, and socially. Both have been presented as frivolous and without true substance, and are thus too often written off as a pursuit, or a person, that is able to contribute to these circles. Fashion is often, and sometimes fairly, said to be the most misogynistic industry of them all, due to its perceived mission statement of transforming bodies to their most palatable form. As a result of this, I believe that fashion is a challenging, interesting, and subversive medium for this discussion to take place within. 𝘗𝘭𝘦𝘢𝘴𝘦 𝘓𝘪𝘬𝘦 𝘔𝘦 is a visual representation of my impatience with the unreasonable and unrealistic standards women are held to, both in mass media and everyday life. It comes from a place of fatigue, irritability, and frustration. It is, and I am, disenchanted with the prospect that anything can or will change. It merely wants to be seen and heard- an opportunity denied to so many women, for so long.
Figures 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 27, 29, 34 & 36 removed for copyright reasons. They may be accessed via the links provided on pages 54-56 of the exegesis.
Keywords: Norquay, Tess -- Criticism and interpretation; Fashion -- Social aspects -- 21st century; Social media -- Psychological aspects; Women in popular culture; Commodification; Misogyny